Evaluation of user experience and satisfaction with workplace-based assessments (WPBAs) in dental postgraduate programs - Ali, Faiza; Muhammad Maaz; Sukhia, Rashna Hoshang; Mubassar Fida (Journal of the Pakistan Medical Association, 2024)
Objectives: To explore the experience of and satisfaction with workplace-based assessment tools among dental postgraduate trainees. Method: The cross-sectional study was conducted from March to October 2022 at the Aga Khan University Hospital, Karachi, and comprised all Operative Dentistry, Prosthodontics and Orthodontics postgraduate trainees. A questionnaire with both open-ended and closed-ended questions was used to record the experiences and satisfaction level of the dental residents who had earlier been subjected to workplace-based assessment. Data was analysed using SPSS 20, while thematic analysis was used for open-ended questions. Results: Of the 20 Subjects, 15(75%) were females. Also, 11(55%) participants had received prior training for workplace-based assessment. There were 16(80%) residents who were satisfied with workplace-based assessment tools in the dental residency programme, 15(75%) agreed that the tools improved their clinical skills and helped them identify their weak areas, all the 20(100%) participants said the feedback given to them was constructive, 18(90%) reported that they were allowed to put in their views. However, 7(35%) participants reported that being observed adversely affected their performance. Conclusion: Dental residents generally gave positive feedback related to workplace-based assessment tools in a clinical setting. Key Words: Dental residency, Clinical competence, Teaching.